Pengaruh Cara Belajar Matematika Siswa SMP Terhadap Prestasi Belajar Siswa di Masa Pandemi - Salma Hakiim; Halimatus Sadiyah (Departement of Mathematics Education, 2022)
Abstract Education during this pandemic is a challenge for all parties. Students are required to get good learning outcomes during online learning. The students achieving these learning outcomes are by applying their respective ways of learning. This study aims to determine the effect of JHS students way of learning on learning outcomes. This type of research is survey research with a quantitative approach. The subjects is 36 students of Wahid Hayim JHS in grades 7, 8 and 9 for 2021/2022 academic year with using simple random sampling technique. The instrument in this study was questionnaire way of learning which adopted from the questionnaire way of learning in the thesis title The Effect of Learning Mathematics on Mathematics Learning Achievement in Grade IV Elementary Schools throughout the Imam Bonjol Cluster, Purbalingga District by Rofiqoh Nur Rokhmah which was valid and reliable. The questionnaire was distributed in the google form. The data of a database of students' midterm semester scores as well as research instruments. Analysis of the data is use descriptive statistical analysis and simple linear regression analysis. The results of this study indicate that the way of learning does not affect the learning outcomes achieved by students. Abstrak Pendidikan dimasa pandemi ini merupakan tantangan semua pihak. Siswa dituntut mendapatkan hasil belajar yang tetap bagus selama pembelajaran daring. Upaya siswa dalam mencapai hasil belajar tersebut dengan menerapkan cara belajar masing-masing yang sesuai dengan siswa. Penelitian ini bertujuan mengetahui pengaruh cara belajar siswa SMP terhadap hasil belajar. Jenis penelitian ini adalah penelitian survey dengan pendekatan kuantitatif. Subjek dari penelitian ini adalah sebanyak 36 siswa SMP Wahid Hayim kelas 7,8 dan 9 tahun ajaran 2021/2022 dengan sampel diambil menggunakan teknik simple random sampling. Instrumen dalam penelitian ini berupa angket cara belajar yang diadopsi dari angket cara belajar di skripsi Pengaruh Cara Belajar Matematika Terhadap Prestasi Belajar Matematika Kelas IV SD Se-Gugus Imam Bonjol Kecamatan Purbalingga oleh Rofiqoh Nur Rokhmah yang telah valid dan reliabel. Angket tersebut disebar dalam bentuk google form. Data berupa database nilai UTS siswa juga instrumen penelitian. Analisis datanya berupa analisis statistik deskriptif dan analisis regresi linear sederhana. Hasil dari penelitian ini menunjukkan bahwa cara belajar tidak berpengaruh terhadap hasil belajar yang dicapai siswa.